Effects of different storage temperatures on the properties of nonlatex orthodontic modules - Shivam Sharma; Ashish K Singh; Puneet Batra; Nitin Arora; Sridhar Kannan (Wolters Kluwer Medknow Publications, 2022)
Objective: To evaluate and compare the effect of variation in storage temperatures and duration on a tensile load at failure of elastomeric modules. Methods: In total, 140 modules were used in the study, 20 of which were tested on day 0 as received from a company using a Universal testing machine for baseline estimation of tensile load at failure. The rest 120 modules were divided into 6 groups. Groups I, II, and III modules were stored at low (T1 = 1-5°C), moderate (T2 = 20-25°C) and high (T3 = 35-40°C) temperatures, respectively, for 6 months. Groups IV, V and VI modules were stored at temperatures T1, T2 and T3 for 1 year, respectively, and were tested for tensile load at failure. Results: The tensile load at failure for the control group was 21.588 ± 1.082 N and for 6-month interval at temperatures T1, T2 and T3 was 18.818 N ± 1.121 N, 17.841 N ± 1.334 N and 17.149 N ± 1.074 N, respectively, and for 1 year, it was 17.205 N ± 1.043 N, 16.836 N ± 0.487 N and 14.788 N ± 0.781 N, respectively. The tensile load at failure decreased significantly from 6 months to 1 year among each temperature group. Conclusions: Maximum force degradation was seen in modules at high temperature followed by medium temperature and low temperature at both 6 months and 1 year intervals, and tensile load at failure decreased significantly from 6 months to 1 year storage duration. These results conclude that the temperature and duration at which the samples were exposed during storage produce a significant change in the forces exerted by the modules.